SELF-MURDER AND SELF-MURDERERS IN SOCIAL REPRESENTATIONS OF YOUNG RUSSIANS: AN EXPLORATORY STUDY - Nikolay Dvoryanchikov; Inna Bovina; Olesya Vikhristuck; Elizaveta Berezina; Gennady Bannikov; Inga Konopleva (Psichologija, 2015)
Premature death caused by self-murder is one of the most serious problems of public health in the world. About one million people disappear for this reason each year, and the further estimations are quite pessimistic. There are no doubts that the current situation is extremely serious and complex; as a result, the importance of the further development and realization of the preventive measures is obvious. Each preventive program in the field of public health should be based on the results of social psychological studies concerning the problem. In the presented paper, we discuss the results of the exploratory study based on the ideas of the social representations theory. The objective of the exploratory study was to analyze the specificity